2020
DOI: 10.1177/1073191120939155
|View full text |Cite
|
Sign up to set email alerts
|

Bias-Variance Trade-Off in Continuous Test Norming

Abstract: In continuous test norming, the test score distribution is estimated as a continuous function of predictor(s). A flexible approach for norm estimation is the use of generalized additive models for location, scale, and shape. It is unknown how sensitive their estimates are to model flexibility and sample size. Generally, a flexible model that fits at the population level has smaller bias than its restricted nonfitting version, yet it has larger sampling variability. We investigated how model flexibility relates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…It simplifies to the normal distribution when ν = 1 and τ = ∞. In a simulation study (Voncken et al, 2020), it appeared problematic to estimate the reparametrized version of the skew Student t distribution for simulated data sampled from a normal population, presumably because of extremely large estimated τ parameters. The distribution could be estimated well for skewed data.…”
Section: Regression-based Norming With Gamlssmentioning
confidence: 99%
See 4 more Smart Citations
“…It simplifies to the normal distribution when ν = 1 and τ = ∞. In a simulation study (Voncken et al, 2020), it appeared problematic to estimate the reparametrized version of the skew Student t distribution for simulated data sampled from a normal population, presumably because of extremely large estimated τ parameters. The distribution could be estimated well for skewed data.…”
Section: Regression-based Norming With Gamlssmentioning
confidence: 99%
“…The sensitivity of certain GAMLSS norm models (i.e., involving normal, skew Student t , and BCPE distributions) to different forms and sources of model misspecification has been examined in a simulation study (Voncken et al, 2020). This study showed that models with too strict distributional assumptions yield biased estimates, whereas too flexible models yield increased variance.…”
Section: Regression-based Norming With Gamlssmentioning
confidence: 99%
See 3 more Smart Citations